Business continuity management system : a complete framework for implementing ISO 22301 - Wong, Wei Ning Zechariah; Shi, Jianping (Kogan Page, 2015)
"A Business Continuity Management System (BCMS) is a management framework that creates controls to address risks and measure an organization's ability to manage disruptions. The International Standard, ISO 22301, helps protect against the threats, including natural disaster, IT failure, staff illness, terrorist threat or a disruption in the supply chain. It provides a framework for assessing critical suppliers and their associated risks, assessing current business practices and planning contingency measures, so when disruptions happen, businesses are prepared and able to respond effectively.Business Continuity Management System offers a complete guide to implementing a fit-for-purpose resilience capability in any organization. Structured in line with ISO22301 and with a focus on performance improvement throughout, chapters cover developing, establishing and operating a BCMS initiative. Built upon the principles of the International Standard and current best practice, with a practical focus on theories and models, this book offers an objective, thorough solution for the practitioner. "--Resumé vydavatele